Lestegás Tizón, Iago. O paradoxo do turismo. Sermos Galiza, Santiago de Compostela, 2025, 62 pp. ISBN: 9788409736133 - Pereiro, Xerardo (Investigaciones Turísticas, 2026)
RESEÑA BIBLIOGRÁFICA -Lestegás Tizón, Iago. O paradoxo do turismo. Sermos Galiza, Santiago de Compostela, 2025, 62 pp. ISBN: 9788409736133